WEBTOON: A Phenomenological Study on Reading Preferences Among Senior High Students in Quirino National High School - Ramos, Jun-Jun (International Journal of Arts, Sciences and Education, 2022)
This research aims to find out the experience of Senior High School students in the webtoon. They read webtoon as their reading preference in Quirino National High School, Quirino, Isabela, Philippines. The researcher used the phenomenological design of research. The researcher used an individual direct interview in gathering data. The researcher used purposive sampling using narrative analysis. The researcher found that ESL senior high students used webtoon as reading material because of its availability, trend, ease of use, and access to gadgets and internet connection. They are also entertained in reading webtoon because they can use their extra time effectively and educationally by reading webtoon. Webtoon is a great tool to enhance their reading skills. Students use webtoon as reading material for them to improve their vocabulary or to learn new words. Through this, they can discover something new such as cultures and traditions shown in a story, making them aware of what’s happening around them.